(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The aesthetic functions of city parks, their role in the formation of a pleasant visual environment and the preservation of the historical memory of society are considered. Using the example of the city of Osh, methods for assessing the qualitative, quantitative and aesthetic functions of landscapes are shown, which makes it possible to make economic arguments in favor of their conservation.